A comparative study of performance of commercial banks in ASIAN developing and developed countries - Asima Siddique; Omar Masood; Kiran Javaria; Dinh Tran Ngoc Huy (Insights into Regional Development)
The main focus of this study is to investigate the impact of non-performing loans (NPLs) and other bank specific factors on the financial performance of commercial banks in Asian developing and developed countries due to an alarmingly high ratio of non-performing loans.The bank specific factors that are used in this study are cost efficiency ratio (CER), capital adequacy ratio (CAR), size of the bank, sales growth (SG) and proxies of financial performance (FP) are return on equity (ROA) and return on asset (ROE). Secondary Panel data of ten years (2006-2015) has been used for this empirical analysis and 19 commercial banks from developing countries of Asia (Pakistan and India), while 17 commercial banks from developed countries of Asia (Japan and Saudi Arabia) are selected. Generalized method of moment is used for the coefficient estimation to overcome the effects of some endogenous variables. NPLs and CER are significantly negatively related to the financial performance (ROA and ROE) of developing and developed countries commercial banks. There is a negative relationship of bank size with most of financial performance variables. Sale growth and capital adequacy ratio has significant positive relationship both measures of financial performance (ROA and ROE) in both pools. Due to the importance of commercial banks in the overall economy of a country, there is a need for management of commercial banks and regulatory authorities to undertake policies that ensure efficiency in banking operations.